Branding UMKM yang terdampak Covid-19 di Desa Mandirancan, Kec. Kebasen, Kab. Banyumas - Adryan Alif Naufal (PT. Gyandharma Global Media, 2025)
The Covid-19 pandemic has significantly impacted various aspects of life, including the economy of residents, particularly MSMEs in Mandirancan Village. One of the objectives of the Thematic Community Service Program (KKN) in Mandirancan Village, Kebasen District, Banyumas Regency, was to help increase sales of MSMEs affected by Covid-19 by branding through social media. The methods used were Participatory Learning and Action, Participatory Rural Appraisal, and information gathering through interviews. The results of this activity have had at least a small tangible impact on MSMEs in Mandirancan Village affected by Covid-19, especially in terms of sales.